TRANSLATION IN A BILINGUAL SITUATION - Spilka, Irène V. (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 1978)
Whenever people of different languages have to conduct translations, there is a role for the specialist who can interpret and for the one who can translate. The form and content of messages in a given language interacting as they do; and the modes of communicating content as well as the forms of separate languages differing as they do; the translator is faced with a task calling for an equal sophistication of skills and delicacy of understanding in each language, and yet must maintain a personal resistance to their tendency to mingle in his own mind. Spilka, emphasizing the need for training in a demanding profession, illustrates and categorizes the characteristic problems facing the translator, with some especial mention of those peculiar to Canada and Quebec.